Multifactor transcriptional profiling of potato during 2,4-D-induced resistance to common scab disease - Fabian, Matthew L.; Nguyen, Hien P.; Stommel, John R.; Clarke, Christopher R. (Frontiers in Plant Science, 2025)
Foliar application of low-dose 2,4-dichlorophenoxyacetic acid (2,4-D) has been demonstrated to reduce potato common scab disease caused by phytopathogenic Streptomyces. Foliar-applied 2,4-D is translocated to the tubers but does not cause direct toxicity against the pathogen. The efficacy of 2,4-D treatment for common scab disease management is inconsistent among field trials in the literature, and the exact mode of action is unknown. Here, we identified transcriptomic responses of potato to low-dose 2,4-D treatment in the presence and absence of the pathogen and in tuber periderm and foliar tissue. Pathogen infection primarily altered transcriptomic responses in tuber periderm tissue, while foliar 2,4-D application caused larger shifts in gene expression in leaf tissue, as expected. Gene ontology (GO) terms associated with pathogen defense, stress responses, and enzymatic inhibitors were significantly enriched among differentially expressed genes in the tuber response to the pathogen. There were more differentially expressed genes and enriched GO terms in response to the pathogen when plants were treated with 2,4-D than in the non-2,4-D-treated plants, including differentially expressed genes and GO terms related to lipases, jasmonic acid signaling, and transport. Fewer differentially expressed genes were identified in tuber tissue than in leaf tissue following foliar 2,4-D treatment, but GO terms related to sucrose transport were enriched in tuber RNA samples from 2,4-D-treated, non-inoculated plants. Altered glucose and fructose, but not sucrose, levels in tuber medulla and periderm tissue, the site of common scab infection, were observed in 2,4-D-treated plants. Utilizing multiple factors, i.e., mock or 2,4-D treatments in both the presence and absence of the pathogen, in parallel transcriptional profiling experiments enabled the identification of pathways that directly respond to 2,4-D treatment in both foliar and tuber tissue and pathways with altered response in the context of pathogen infection. Identifying tools to more consistently induce these changes may enable more robust disease management than indirect foliar 2,4-D treatments.